Impactos de responsabilidad social-Fundación Universitaria Monserrate (2012)
ABSTRACT: This article is interested in analyzing the curricular components that recognize university social responsibility (USR) in the Monserrate University Foundation (Fundación Universitaria Monserrate-FUM), identifying its impact on students, teachers and the community in general and the way it promotes social transformation. Methodology of a qualitative character is implemented, allowing the research subjects to give testimonials of their experiences with the intention of revealing the changes or impacts generated by social responsibility practices, in the light of the proposal by Vallaeys (2004; 2007). In general terms, significant evidence was found that USR is perceived as one of the defining elements for the identity of the educational project itself, given that a strong cohesion and adherence to values and principles promoted by the university can be noted.